Extraction process of essential oil from plectranthus amboinicus using microwave-assisted hydrodistillation and evaluation of it’s antibacterial activity - Dao, Tan Phat; Nguyen, Duy Chinh; Nguyen, Duy Trinh; Tran, Thien Hien; Nguyen, Phu Thuong Nhan; Le, Nhan Thi Hong; Le, Xuan Tien; Nguyen, Dai Hai; Vo, Dai-Viet N.; Bach, Long Giang (Asian J. Chem, 2019)
Plectranthus amboinicus oil has many applications in pharmaceutical, medicine and cosmetic industries. Recently, new methods of extracting essential oil used have been increasingly developed to replace traditional methods. In this study, maximization of essential oils yield from P. amboinicus was studied by the combination of microwave assisted hydro-distillation (MAHD) and response surface methodology (RSM). We found that that the maximum essential oil yield was 0.1374 % with 94.38 % reliability and influencing factors such as microwave power for this process was 515 W, raw material to water ratio 1.64:1, extraction time at 100.8 min. ANOVA analysis for quadratic model also gives favourable outcome including the high determination coefficient (R2 = 0.94), significant F-value and p-value of coefficients. Under laboratory condition, the obtained yield (0.1374 %) approximated the yield predicted by the quadratic model, suggesting the reasonable soundness of the employed model and RSM when it comes to optimizing the parameters of extraction. In addition, considerable antibacterial activities of extracted essential oil against four bacteria cultures, in particular, S. aureus was recognized.